2014
DOI: 10.1002/maco.201307422
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of alumina‐forming austenitic steel in molten nitrate salts by gravimetric analysis and impedance spectroscopy

Abstract: In recent years, the study of renewable energies and its practical application has increased significantly. Solar energy feasibility entails the development of energy storage systems since solar power plants need to be working in unfavorable weather or night periods. The main heat transfer fluid (HTF) used on these plants is a salt mixture of 60% NaNO3/40% NaNO3 which must be kept above 220 °C to prevent freezing. This high operating temperature causes corrosion problems for steels in contact with the HTF, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 18 publications
(24 reference statements)
1
42
0
Order By: Relevance
“…It was shown that the corrosion products include iron‐chromium spinel (FeCr 2 O 4 ) formed via reaction (Eq. ) at the inner side and sodium ferrite (NaFeO 2 ) at the outer side of the oxide scale . The latter does not behave protective and can form as a result of reaction between the hematite and Na 2 O traces existing in molten salt (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the corrosion products include iron‐chromium spinel (FeCr 2 O 4 ) formed via reaction (Eq. ) at the inner side and sodium ferrite (NaFeO 2 ) at the outer side of the oxide scale . The latter does not behave protective and can form as a result of reaction between the hematite and Na 2 O traces existing in molten salt (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Goods and Bradshaw [15] have reported a corrosion rate value of [6][7][8][9][10][11][12][13][14][15] lm per year at 570°C for two different stainless steels (SS-304 and SS-316) and 5 lm per year at 316°C for a carbon steel (A36), in contact with 'Solar Salt'. Using gravimetric immersion method, corrosion issues caused by Solar Salt at 390 and 550°C have been studied by Fernandez et al [16], on two different stainless steels (types AISI 304 and 430) and low-Cr ($2%) alloy steel (T22). It has been found that the alloy T22 underwent greatest mass gain as expected for a low Cr content steel, whereas alloys 304 and 430 showed almost zero gain/loss of mass with immersion time up to 2000 h.…”
Section: Introductionmentioning
confidence: 99%
“…The (Fe, Cr) 3 O 4 spinel formed via the following reactions: 2Cr+3O23Cr2O3+6e Fe+Cr2normalO3+normalO2FeCr2normalO4+2normale.…”
Section: Resultsmentioning
confidence: 99%